Development of Coding-Based Learning Tools to Enhance Beginning Writing Skills - Risnadyatul Hudha, Rifqi; Rahmah Purwahida; Eva Amalia; Nanda Veruna Enun Kharisma; Delfia Ikhlasiah Rahman (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2026)
This study aims to develop coding-based learning media to improve the beginning writing skills of elementary school students, especially grades 1 and 2. The background of this study is the low basic writing skills of students and the limited use of technology in writing learning. The study used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were grades 1 and 2 elementary school students and teachers involved in the limited trial. Data collection was carried out through observation, interviews, questionnaires, and writing skills tests in the form of pre-tests and post-tests. The results of the study indicate that the developed coding-based learning media has interactive features, direct feedback, video tutorials, and gradual writing exercises starting from bolding lines, letters, syllables, to simple sentences. The media trial showed an increase in students' beginning writing skills, both in letter writing accuracy, neatness, use of spacing, and the ability to construct simple sentences. In addition, students became more motivated, active, and confident in participating in learning. Thus, coding-based learning media is declared effective and suitable for use as a learning innovation to support the improvement of beginning writing skills in elementary schools.